Using the Braess Paradox to Teach Tacit Negotiation. (December 2016) - Merlone, Ugo; Romano, Angelo
Background. Social dilemmas are situations in which following personal interest leads to collective disasters. Pollution, tropical deforestation, and the sustainable use of natural resources, can be characterized as examples of social dilemmas. In the negotiation literature, social dilemmas are known as tacit negotiations as individuals negotiate through moves rather than verbal communication. These negotiations are difficult to manage because of the absence of binding contracts and the interdependent nature of decisions of the parties involved. Therefore, it is important for participants to learn from activities addressing these issues. Although several negotiation exercises are available, it is difficult to find educational games or simulations specifically devised to allow several participants to face social dilemmas. Purpose. In this article, we present a negotiation game based on a well-known social dilemma, the Braess paradox. The Braess paradox has been observed in many real situations and is particularly suited to highlight the core concepts of social dilemmas. Approach. We will review the main negotiation activities focusing on the number ofparticipants they are implemented for. Then we will present an activity which allows to accommodate up to thirty participants and allows them to understand some interesting aspects of social dilemmas. Findings. Through the lessons gained by experiential learning, and the discussions emerging during debriefing, this activity may provide participants with a better understanding of urgent real problems.